2014
DOI: 10.2147/ijn.s62599
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan gel containing polymeric nanocapsules: a new formulation for vaginal drug delivery

Abstract: The vaginal route of administration is an alternative for several treatments for either local or systemic pharmacological effects. However, the permanence of a drug in this route represents a challenge for formulation development that can be overcome by using nanoencapsulation and chitosan gel. Thus, this work aimed to evaluate the performance of chitosan hydrogels containing cationic and anionic acrylic-based nanocapsules (Eudragit ® RS 100 and Eudragit ® S 100, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…The zeta potential was found to be +9.8±1.5 due to the cationic properties of Eudragit RS 100®, used as nanocapsule shell. The positive zeta potential can increase the contact of the nanocapsules with the skin, due to negative charge of the tissue, as previously observed for the vaginal mucosae (29). The value obtained for the pH was 5.8±0.9, which is in agreement with previous similar nanocapsule aqueous suspensions (30).…”
Section: Nanoparticle Propertiessupporting
confidence: 91%
“…The zeta potential was found to be +9.8±1.5 due to the cationic properties of Eudragit RS 100®, used as nanocapsule shell. The positive zeta potential can increase the contact of the nanocapsules with the skin, due to negative charge of the tissue, as previously observed for the vaginal mucosae (29). The value obtained for the pH was 5.8±0.9, which is in agreement with previous similar nanocapsule aqueous suspensions (30).…”
Section: Nanoparticle Propertiessupporting
confidence: 91%
“…However, the particles used showed some irritancy in vivo. Solid Eudragit RS 100 and Eudragit S 100 nanoparticles measuring 200 nm were incorporated into a chitosan gel by Frank et al [93]. It was found that incorporating nanoparticles into a 2.5 % chitosan gel improved adhesion to porcine vaginal mucosa, as determined using a texture analyser.…”
Section: Gels Containing Particulates For Modulated Drug Deliverymentioning
confidence: 99%
“…The main advantage of this type of polymer is the positive charge that increases the capacity of mucoadhesion, residence time for prolonged release, and, above all, increased penetration capacity in the vaginal mucosa, unlike other nanocapsules, regardless of the gel in which it is incorporated. The formulation reached a depth of up to 3800 µm in the vaginal mucosa [ 70 ].…”
Section: Nanoparticles Prepared From Synthetic Non-biodegradable Pmentioning
confidence: 99%
“…Chitosan is nontoxic, biocompatible, biodegradable, possesses good mechanical properties, good film-forming ability, and is bioadhesive; also, fungicidal and antimicrobial properties have been found. Frank et al [ 70 ] found that gels with a chitosan concentration of 2.5% w / w were those most suitable for vaginal delivery. Chitosan hydrogels exhibited higher adhesion to vaginal mucosa; in addition, the study indirectly revealed low interaction between the vehicle and the fluorescent-marked Eudragit ® RS nanoparticles because penetration of the lipophilic molecule model into the mucosa was high in comparison to when this was not nanoencapsulated.…”
Section: Vehicles For the Administration Of Polymeric Nanoparticlementioning
confidence: 99%